Pendampingan Pengembangan UMKM pada Produk Stik Terigu Barokah Jaya di Desa Kedungbanteng Ponorogo - Dwicahyo, Agung; Anshori, Hudan Ngisa; Kamaluddin, Imam; Azizi, Mujadid Qodri; Mubarak, Dicky Syahar; Sasongko, Yogi Banar (Abdimas Indonesian Journal, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in local economic growth. One of the main challenges faced by MSMEs is the development of innovative products and marketing to be able to compete in the market. This mentoring program aims to improve the quality and competitiveness of Barokah Jaya Flour Stick products in Kedungbanteng Village, Ponorogo, through the application of product innovation concepts, marketing strategies and MSME development. The service methods used include planning, implementation, evaluation and monitoring approaches. The planning stage includes analysis of needs and product development potential. At the implementation stage, product innovation training, strengthening marketing strategies, and business management assistance are carried out. Evaluation is carried out to assess the effectiveness of the program, while monitoring aims to ensure the sustainability of the mentoring impact. The results of this program show an increase in product quality through material and packaging innovation, as well as market expansion through digital marketing strategies. This assistance is expected to strengthen the competitiveness of MSMEs and make a real contribution to the economic empowerment of local communities.